Analisis Struktur Fisik dalam Kumpulan Puisi Doa untuk Anak Cucu Karya W.S Rendra - Firza Humaira; Siti Aisyah Hanim; Rani Ardesi Pratiwi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to describe the physical structure in the poetry collection Doa untuk Anak Cucu (Prayer for Children and Grandchildren) by W.S. Rendra. The research method used is descriptive qualitative with a content analysis approach. The data analyzed are the lines of poetry in the anthology. In-depth, this thesis analyzes the physical structure of the poems in ten selected works from the Doa untuk Anak Cucu collection by W.S. Rendra. The analysis focuses on seven elements of the physical structure of the poems: diction, imagery, figurative language, concrete words, typography, rhyme, and rhythm. The results show that the poet employs various strategies in selecting and arranging the physical elements of the poems. The diction chosen is highly diverse, with a total of 192 words across the ten poems. Imagery, which is strong and present in every poem, amounts to 161 images throughout the collection, creating vivid mental pictures for the reader. Figurative language such as metaphor, simile, and personification is used effectively to enrich the meaning and beauty of the poems, with 152 instances of figurative language identified in the study. The carefully chosen concrete words help readers visualize the objects and events described, with 121 concrete words found in this thesis. The typography used is also varied, with the arrangement of words and lines intentionally set to create specific rhythmic and visual effects. Rhyme and rhythm in the poems create a distinct harmony and musicality. This thesis identifies 121 rhymes and 170 rhythms.